Adverbia Penanda Aspek dalam Novel Sansai karya Ermanto: Suatu Kajian Morfologi - Andayani, Zri; Liusti, Siti Ainim; Zulfariati, Zulfariati (Jurnal Bahasa dan Sastra, 2024)
This study examines the use of adverbial aspect markers in Ermanto's novel Sansai, aiming to revitalize Minangkabau literature by focusing on both cultural and social issues. The research explores how aspect markers influence narrative understanding and temporal dynamics in contemporary Minangkabau prose. Through qualitative document analysis using the Indonesian Language Corpus Linguistic Method (KORTARA), the study identifies and classifies adverbs that denote actions, events, situations, and traits in various temporal contexts. The analysis reveals four types of aspect markers: durative, perfective, imperfective, and inchoative. The novel contains 476 adverbial aspect markers, distributed as follows: 73 durative ("middle"), 64 imperfective ("not yet"), 278 perfective ("already"), and 61 inchoative ("beginning") markers. The perfective aspect "already" emerges as the most frequently used, suggesting a narrative emphasis on completed actions or states. This linguistic analysis provides insights into the narrative structure and temporal nuances of contemporary Minangkabau literature, contributing to a deeper understanding of how language use shapes storytelling and cultural expression. The findings offer a foundation for further exploration of the relationship between linguistic features and literary techniques in regional Indonesian literature.